LINGUODIDACTIC ASPECTS OF ANALYZING MODERN PROSE: FROM LITERARY DISCOURSE TO A DYNAMIC WORLDVIEW (Spectrum Journal of Innovation, Reforms and Development, 2026)
This paper addresses the challenge of integrating contemporary literary texts into the practice of teaching Russian as a foreign language. The author analyzes how subjective nomination and artistic heterotopias form an understanding of changing Russian reality in the minds of foreign students.